Concepções e práticas de leitura na educação de jovens e adultos: o que revelam os memoriais de estudantes do IFPB - Campus Cajazeiras. - Bandeira, Francisca Vera Célida Feitosa (2011)
This academic investigation research concerns our remarks on experienced difficulties from Young and Adult Education students, in their trial to practice the act of reading and writing proficiently. These unrests go from our experience as a Portuguese Language Teacher in Secondary School, at ProgramaNacional de Integração da EducaçãoProfissional with the Basic Education in a Young and Adults Education Modality Technical and Professional Education in Middle Level / Secondary School PROEJA, for a period of two years in the city of Boa Vista, state of Roraima, from Febrary 2005 to June 2006, and from 2007, in the town of Cajazeiras, state of Paraíba. Our discussions are centred on the question of reading experienced by students from the Integrated Technical Course in Middle Level Qualification, Microcomputers Operation at Instituto Federal da Paraíba (IFPB) Campus of Cajazeiras in a Young and Adults Education Modality. For that purpose we used as an investigative instrumental reading memos produced from recorded interviews with six students of the referred course, aiming at investigating, broad outlines, the concepts and practices of reading assumed by collaborators, in order to plot each of the individuals profiles of our research, for understanding socio-economic and cultural contexts in which they are embedded, relating them to the necessities imposed by technological advances of the modern world, in a frequent dialogue with theoretical collaboration of authors such as Freire (1996, 1999, 2000, 2008), Foucambert (1994), Soares (1991), Tfouni (1995), Zilberman (1991), Kalman (2003) and other theorists who introduce the basic principles in the process of reading and writing understanding. We testified, broad outlines, the necessity of including and expanding in the educational setting the awareness of the importance and relevance of the structure of an access policy, concrete and material, to reading and cultural goods that embody the literate world, as an element of public policy which enables the individuals to fruition, socialization, as well as modes of representation and the real significance, specially in what concerns people embedded in a Young and Adults Education context, which for a number of reasons were unable to continue their educational path, and return to school even knowing the limits and difficulties they would face.